1978
DOI: 10.1029/ja083ia11p05277
|View full text |Cite
|
Sign up to set email alerts
|

Quiet time pattern of auroral arcs for different directions of the interplanetary magnetic field in the YZ plane

Abstract: Quiet time arcs observed from the Greenland all‐sky camera network have been ordered in corrected geomagnetic latitude/time mass plots according to the values of the Y and Z components of the IMF. Two different patterns of discrete quiet arcs occur. In one system the arcs are ordered along the statistical auroral oval; in the other, which we have called the polar cap pattern of discrete arcs, the arcs are ordered partly in the sun‐earth direction over the polar cap, especially on the dawnside of the pole, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…It is also clearly seen that most of the arcs (≈70 %) were observed when the IMF was directed northward (0°< CA < 90°and 270°< CA < 360°). Early studies by Berkey et al [1976] and Lassen and Danielsen [1978] found good correlation between IMF B z northward conditions and appearance of polar cap arcs. Our statistical results are basically consistent with their earlier finding.…”
Section: Resultsmentioning
confidence: 99%
“…It is also clearly seen that most of the arcs (≈70 %) were observed when the IMF was directed northward (0°< CA < 90°and 270°< CA < 360°). Early studies by Berkey et al [1976] and Lassen and Danielsen [1978] found good correlation between IMF B z northward conditions and appearance of polar cap arcs. Our statistical results are basically consistent with their earlier finding.…”
Section: Resultsmentioning
confidence: 99%
“…Velocity shear and the corresponding vorticity are such that upward field-aligned currents and associated precipitating electrons occur for positive vorticity. We believe that polar cap arcs, which fill the polar cap for B z north [Lassen and Danielsen, 1978], are the signature of positive vorticity (W) since W z = (r  V z ) = J || [Kelley, 2009]. Thus, the arcs show the input scales for 2-D turbulence, which, as argued next, contribute to the PCP for B z north.…”
Section: Discussionmentioning
confidence: 92%
“…[6] The second type of polar cap aurora was reported by Lassen and Danielsen [1978] and is shown in Figure 2. These multiple arcs were synthesized from all-sky camera data over many years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lassen and Danielsen (1978) have demonstrated that the occurrence of the arcs of this type is associated with the northward polarity of IMF while the arcs extending along the oval are associated with the southward IMF polarity. By examining the energy spectrum offions and electrons observed by AE-D, Burch et al (1979) have found indications that thermal electrons are accelerated in the polar cap to > 1 keV when the IMF polarity is northward by a potential difference generated along magnetic field lines.…”
Section: Polar-cap Convection Associated With the Northward Imfmentioning
confidence: 99%